Anti-inflammatory effects of selected dietary components on endometriosis - review - Agata Pawłowska; Piotr Zatyka; Adam Słomczyński; Dominika Opala; Michal Rabenda; Dobromiła Osuch; Piotr Janik (Nicolaus Copernicus University in Toruń, 2024)
Background: Endometriosis is a chronic inflammatory disorder that is among the most common gynaecological problems in women of reproductive age. The disease involves the presence of endometrial tissue outside the uterus, which manifests as pelvic pain and infertility. The main theory for its development suggests that endometrial cells move into the abdominal cavity during menstruation and implant there. This process leads to an increase in inflammatory cells and increased concentrations of cytokines, chemokines and prostaglandins, resulting in chronic inflammation. Objective: The aim of this work is to analyse in detail the available studies on the anti-inflammatory effects of selected dietary components such as polyphenols, vitamin D and omega-3 fatty acids. The work aims to evaluate their potential as future therapeutic options for the treatment of endometriosis, with a critical approach to their efficacy and possible application in the treatment of this disease. Materials and methods: A review of the literature available in the PubMed database was conducted using the following phrases in English: endometriosis, pain, diet, polyphenols, resveratrol, curcumin, vitamin D3, OMEGA-3 acids, polyunsaturated acids State of knowledge: Changing dietary patterns in patients with endometriosis may result in a reduction in levels of inflammatory markers, which are typically elevated in this disease. Polyphenols, such as resveratrol and curcumin, show anti-inflammatory effects and inhibit endometrial cell proliferation. Vitamin D3 shows anti-inflammatory effects and influences angiogenesis. Omega-3 fatty acids may reduce inflammation and endometrial proliferation. Conclusions: The literature review indicates that polyphenols, vitamin D3 and omega-3 fatty acids offer promising therapeutic properties for the treatment of endometriosis, with anti-inflammatory and proliferative, pain-relieving effects. Despite these promising results, further clinical trials are needed.